Konsep Kebijakan Penanggulangan Kasus Teroris Dr. Azhari di Indonesia serta Peristiwa Penghancuran Menara Kembar WTC Amerika Serikat 9/11 Dihubungkan dengan Penguatan Pertahanan NKRI dan Bela Negara - Nasir, Tomi Khoyron; Afdhali, Dino Rizka; Wahyudi, Slamet Tri (Journal Evidence Of Law, 2025)
Terrorism is increasingly attracting public attention, especially with the existence of action of world terrorism that have occurred in several countries, one of which is the United States where the destruction of the twin towers on 9/11 occurred and became the forerunner of terrorist acts in Indonesia. To deal with the issue of national security, building awareness of national defense is one solution that can be done to anticipate terrorist acts occurring in the future. This article discusses the urgency of the Indonesian government to increase awareness of national defense and national defense in overcoming the problem of terrorist acts. The research approach method uses a normative juridical method with a legislative approach and a conceptual approach to examine the problem of terrorist acts in Indonesia. The data source for writing this article comes from a literature study whose sources come from books, papers, and journals related to the law on eradicating terrorism. In making this article, the author discusses how the ideality of handling terror acts in Indonesia over the collapse of the twin towers of 9/11 in the United States and the Dr. Azhari bomb case is connected to the improvement of the defense nation of the Republic Indonesia. The results of this study explain that through increasing awareness of defending the country and national defense, society can be more prepared and able to face the threat of terrorism and build a stronger and more stable Indonesia.